(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1862)
The author discusses the history of the bells that were housed in St Giles cathedral in Edinburgh in the sixteenth and seventeenth centuries. In particular, the article includes transcriptions of contracts between the church and John Meikle for musical bells. Meeting notes for 16 February, 1859 are appended.